Salvage Cryotherapy for Radiation-Recurrent Prostate Cancer: Outcomes and Complications - Finley, David S. (Current Science Inc., 2011)
Potentially curative salvage options for radio-recurrent prostate cancer include prostatectomy, brachytherapy, high-intensity focused ultrasound, and cryotherapy. Salvage cryoablation technology, surgical technique, oncologic outcomes, and complication rates have improved dramatically over the past few decades, shifting this treatment modality from investigational status to an established therapeutic option. In this review, we focus on the most up-to-date oncologic and functional outcomes, as well as complications of salvage cryotherapy for radiation-recurrent prostate cancer.